2017
DOI: 10.1021/acsomega.6b00513
|View full text |Cite
|
Sign up to set email alerts
|

Diketopiperazines as Cross-Communication Quorum-Sensing Signals between Cronobacter sakazakii and Bacillus cereus

Abstract: Herein, we reveal a second quorum-sensing system produced by Cronobacter sakazakii. A cyclo(l-Pro–l-Leu) diketopiperazine, detected in pure and mixed cultures of C. sakazakii and Bacillus cereus explains the coexistence of both in the same industrial environments. The molecule was identified by gas chromatography–mass spectrometry (GC–MS), 1H, and 13C NMR, including 2D NMR (correlation spectroscopy, heteronuclear multiple bond correlation, and heteronuclear single quantum correlation), and the absolute configu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…Indeed, a very recent study showed that an alternative type of QS system exists, a cyclo (L-Pro-L-Leu) diketopiperazine was detected in pure and mixed cultures of C. sakazakii and B. cereus, possibly acting as cross-communication QS signals between these two organisms [121]. 2,5-DKPs are QS molecules commonly found in Gram-positive bacteria and are not usually secreted by Gram-negative microorganisms.…”
Section: Quorum Sensing Signaling Systemsmentioning
confidence: 99%
“…Indeed, a very recent study showed that an alternative type of QS system exists, a cyclo (L-Pro-L-Leu) diketopiperazine was detected in pure and mixed cultures of C. sakazakii and B. cereus, possibly acting as cross-communication QS signals between these two organisms [121]. 2,5-DKPs are QS molecules commonly found in Gram-positive bacteria and are not usually secreted by Gram-negative microorganisms.…”
Section: Quorum Sensing Signaling Systemsmentioning
confidence: 99%
“…Some signals may even lead to crosstalk between different quorum‐sensing systems. An example are diketopiperazines (DKPs), cyclic dipeptides involved in trans‐kingdom interactions of bacteria with eukaryotes and inter‐species signaling between gram‐negative and gram‐positive bacteria . DKPs such as cyclo(ΔAla‐ l ‐Val), cyclo(L‐Pro‐ l ‐Tyr) ( 10 ), and cyclo( l ‐Phe‐ l ‐Pro) were isolated from culture supernatants of various gram‐negative bacteria including Pseudomonads, P. mirabilis , Citrobacter freundii , and Enterobacter agglomerans and recombinant LuxR‐based AHL biosensor assay revealed that they compete with the site of AHL binding and thereby antagonize quorum sensing.…”
Section: Swarming and Bacterial Signalingmentioning
confidence: 99%
“…An example are diketopiperazines (DKPs), cyclic dipeptidesi nvolved in trans-kingdom interactions of bacteria with eukaryotes [46] and inter-species signaling between gram-negative and gram-positive bacteria. [47] DKPs such as cyclo(DAla-l-Val), cyclo(L-Pro-l-Tyr) (10), and cyclo(l-Phe-l-Pro) were isolated from culture supernatantso fv arious gram-negative bacteria including Pseudomonads, P. mirabilis, Citrobacter freundii,a nd Enterobacter agglomerans and recombinant LuxR-based AHL biosensor assay revealed that they competew ith the site of AHL binding and thereby antagonize quorum sensing.C yclo(l-Pro-l-Tyr) (10)r educed swarming of wild type S. liquefaciens as well as of a DswrI mutant for which swarming motilityd ependso ne xternals upply of N-butanoyl-l-homoserine lactone (C4-HSL) (Figure 2, left). [48] In many cases, however,t he cellular targetso fq uorum-sensing inhibitors or their compound classes have not yet been clearlyi dentified.H ereby,p henotypic or transcriptional analyses have often tentatively pointed to interference with AHLbased quorum sensing as likely mechanismofswarming inhibition.…”
Section: Blockingahl Receptorsmentioning
confidence: 99%
“…Purified compounds were placed in silica gel overnight and dried thoroughly, redissolved in deuterated chloroform solution, transferred to a tube, and scanned by nuclear magnetic resonance (NMR) on a Bruker 500 MHz [28]. Signal molecules isolated from S. odorifera fermentation broth were detected by ultra high-performance liquid phase-mass spectra (UHPLC-MS) and HPLC as follows: C 18 reversed-phase column (ZORBAX SB-Aq, 4.6 × 150 mm, 5 µm), methanol and ultrapure water from (20:80) to (55:45), gradient elution for 40 min, injection 10 µL, temperature 25 • C, and flow rate 1 mL/min.…”
Section: Purification and Identification Of Qs Signal Molecules From mentioning
confidence: 99%